2017
DOI: 10.1371/journal.pone.0179018
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of eggplant (Solanum melongena L.) heterostylous pistil development

Abstract: Heterostyly is a common floral polymorphism, but the proteomic basis of this trait is still largely unexplored. In this study, self- and cross-pollination of L-morph and S-morph flowers and comparison of embryo sac development in eggplant (Solanum melongena L.) suggested that lower fruit set from S-morph flowers results from stigma-pollen incompatibility. To explore the molecular mechanism underlying heterostyly development, we conducted isobaric tags for relative and absolute quantification (iTRAQ) proteomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…Observations with the use of a fluorescence microscope allowed us to verify the correct growth of pollen tubes in the styles of all types of pistils but their number was significantly affected by flower type and biostimulant treatment and by cultivar to a lesser extent. This observation is contrary to the results of Wang et al [11], who determined that the structure of the stigmatic surface in short-styled flowers inhibited pollen germination. On the grounds of highly genotype-dependent heterostyly expression in eggplant, results on short-styled pistil performance may be divergent.…”
Section: Heterostyly Expression In Eggplant As Affected By Biostimulacontrasting
confidence: 99%
See 1 more Smart Citation
“…Observations with the use of a fluorescence microscope allowed us to verify the correct growth of pollen tubes in the styles of all types of pistils but their number was significantly affected by flower type and biostimulant treatment and by cultivar to a lesser extent. This observation is contrary to the results of Wang et al [11], who determined that the structure of the stigmatic surface in short-styled flowers inhibited pollen germination. On the grounds of highly genotype-dependent heterostyly expression in eggplant, results on short-styled pistil performance may be divergent.…”
Section: Heterostyly Expression In Eggplant As Affected By Biostimulacontrasting
confidence: 99%
“…The higher fruit setting efficiency of this phenotype results from well-developed nodules with high pollen absorption capacity. However, the development of the ovules and their position in the placenta, as well as pollen grain shape, size, and amount in anthers, were nondifferentiated among long-, medium-, and short-styled pistils [6,10], although Wang et al [11] demonstrated that lower fruit setting from short-styled flowers resulted from stigma-pollen incompatibility. The bumblebee (Bombus terrestris) is the most effective eggplant pollinator for plants under covers.…”
Section: Introductionmentioning
confidence: 99%
“…In angiosperms, various factors affect the successful pollination and subsequent fertilization of the egg in the female gametophyte (i.e., embryo sac). The mating patterns are greatly influenced by the phenotypic variations in floral traits, such as herkogamy (the spatial separation of anthers and stigma) and dichogamy (the temporal separation of male and female phases) [1][2][3][4][5][6][7][8], cleistogamy (the self-fertilization within a permanently closed flower) [3,9], and heterostyly (styles of different lengths relative to the stamens in the flowers of different plants) [10,11]. The diversity of functional floral traits is defined by the genetic and developmental mechanisms controlling the differentiation of these reproductive organs during floral ontogeny.…”
Section: Introductionmentioning
confidence: 99%